ANALISIS KINERJA PEGAWAI DITINJAU DARI ASPEK PENEMPATAN DAN KONFLIK INTERNAL - Tarwijo Tarwijo; Moh. Sutoro; Mukrodi Mukrodi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The organization realizes that the achievement of goals is the result of work performance and productivity. Therefore, placing employees according to their fields is imperative. In addition, reducing various confounding factors that can reduce performance is also a necessity. In fact, this study aims to gather information and describe the factors that can increase and decrease performance. Thus, a knowledge is obtained to overcome it. The research method used quantitative with a total sample size of 69. To obtain data, a number of questions (questionnaires) were asked to the respondents. The collected data were analyzed using multiple regression techniques. The results suggest that employee performance will increase significantly if there is no bully, such as conflict. This means that the factor that significantly hinders the implementation of work and has an impact on decreasing the quality of work results is conflict. Furthermore, the results of the study explained that job placement must be done correctly. This means that a good job placement has an impact on improving performance, based on the conformity aspect, namely competence and personality.